How do women seeking abortion choose between surgical and medical abortion? Perspectives from abortion service providers. (17th August 2016) - Newton, Danielle; Bayly, Chris; McNamee, Kathleen; Hardiman, Annarella; Bismark, Marie; Webster, Amy; Keogh, Louise
Abstract : Background: Depending on availability, many Australian women seeking an abortion will be faced with the choice between surgical or medical abortion. Little is known about the factors that influence Australian women's choice of method. Aim: Through the perspectives of abortion service providers, this study aimed to explore the factors that contribute to Australian women's decision to have a surgical or medical abortion. Materials and Methods: In 2015, in‐depth interviews were conducted with fifteen Victorian‐based key informants (KIs) directly providing or working within a service offering medical abortion. Ten KIs were working at a service that also provided surgical abortion. Interviews were semi‐structured, conducted face‐to‐face or over the telephone, transcribed verbatim and analysed thematically. Results: KIs described varying levels of awareness of medical abortion, with poorer awareness in regional areas. When it comes to accessing information, women were informed by: their own research (often online); their own experiences and the experiences of others; and advice from health professionals. Women's reasons for choosing surgical or medical abortion range from the pragmatic (timing and location of the method, support at home) to the subjective (perceived risk, emotional impact, privacy, control, and physical ability). Conclusions: Women benefit from an alternative to surgical abortion and are well‐placed to choose between the two methods, however, challenges remain to ensure that all women are enabled to make an informed choice. KIs identify the need to: promote the availability of medical abortion; address misconceptions about this method; and increase general practitioner involvement in the provision of medical abortion.